Marketing aspect of commercialization of intelligent technologies at the enterprise - Ievsieiev, A. S.; Pererva, P. G. (WSEH, 2023)
It has been proven that the implementation of the innovation process is associated with the formation of innovation, its development and commercialization. When creating an innovation, its life cycle, competitiveness, and efficiency must be taken into account. An innovation strategy should be aimed at creating a new product that has distinctive features, preferably unique in its field, which will contain its competitive advantages, which will allow the enterprise to be better than its competitors.
Keywords: marketing; commercialization; intelligent technologies; modern economy; markets; innovation; life cycle; competitiveness; enterprises